2020
DOI: 10.1002/hpja.411
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of a Pet Support Program in an Australian university setting

Abstract: Issue addressed: Internationally, universities have recognised the benefits of Pet Support Programs (PSPs). However, existing literature has predominately focused on quantitatively measuring health outcomes associated with a PSP amongst student populations. This research aimed to explore the feasibility of a PSP within an Australian university, as there is a need to explore practical considerations involved in implementation.Methods: This research used a qualitative descriptive approach. Participants were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Barriers identified, especially policy restrictions and the challenges of organising the CSP align with the results of a study conducted at Deakin University in Australia. 22 In that study, it was identified that for CSPs to be implemented there would be a need to review and adapt relevant university policies and address program matters such as suitable locations/facilities as well as cater for animal welfare.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Barriers identified, especially policy restrictions and the challenges of organising the CSP align with the results of a study conducted at Deakin University in Australia. 22 In that study, it was identified that for CSPs to be implemented there would be a need to review and adapt relevant university policies and address program matters such as suitable locations/facilities as well as cater for animal welfare.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the current policy does not allow pets on campus. 22 Thus, if the institution was to implement a CSP, its current policy needs to be reviewed and adapted, which in turn calls for political commitment and the need to secure it from the onset. 1 The concern about animal welfare is echoed by pet owners, handlers, and animal welfare groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations